A comparative study and optimization of phase change material based heat sinks for thermal management of electronic components. (November 2021) - Kumar, Anuj; Kothari, Rohit; Sahu, Santosh K.; Kundalwal, Shailesh I
Highlights: Metallic and non-metallic foam are used to enhance the heat transfer in PCM. Effect of heat flux and volume fraction of PCM and TCE is investigated. Maximum 17.47% reduction in temperature is observed for 5% TCE compared to 25%. HSSPF takes 13.7% lesser time for 35 °C SPT compared to HSNF during solidification. VIKOR method is employed for finding the best heat sink configurations. Abstract: Present paper reports the thermal performance of phase change material (PCM) based heat sinks (HSs) with foams (metallic and non-metallic) and HS with fins and without fins. The effect of volume fraction of thermal conductivity enhancer (TCE), volume fraction of PCM, and input heat flux values ( q ″  = 1.5–2.5 kW/m 2 ) on the performance of PCM-based HS are studied through experimental investigation. At q ″  = 1.5 kW/m 2, the enhancement ratio in operating time for PCM-based HS with carbon foam (CF) and PCM-based HSNF is found to be 5.5 and 2.73 times higher compared to HS with no PCM. For PCM-based HS with CF, the reduction in base temperature is found to be 17.47% with 5% TCE compared to 25% TCE. During discharging process, HSSPF exhibits 13.7% less time to reach SPT of 35 °C in comparison to HSNF filled with PCM. A multi attribute decision-making optimization technique (VIKOR method) is employed to find the best HS configuration, and it is found that the PCM-based HS with CF can be utilized for the effective cooling of electronic components. Graphical abstract: Image, graphical abstract